Effects of 3D printing parameters on mechanical properties of ABS samples - Ahmad, Mohd Nazri; Yahya, Abdullah (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The most modern technique utilized to create intricate manufactured parts for a variety of applications is called additive manufacturing (AM). Fused deposition modeling (FDM) has been acknowledged as the greatest consideration in the development and industrial sectors. The main objective of this study was to investigate how printing factors affected the mechanical characteristics of printed samples. Samples were produced via an FDM 3D printer in compliance with an ASTM D638 using a variety of input settings, including orientation, layer thickness, speed, and infill pattern. Tensile tests and morphological analysis using a scanning electron microscope (SEM) were done on the printed samples. The results of this study demonstrate that factors including layer thickness, printing speed, and orientation significantly affect the tensile strength of the ABS-printed samples. The 45◦ orientations, 0.3 mm thickness, and normal speed had a significant impact on the tensile strength of the ABS-printed samples. On the other hand, samples with a 90◦ orientation, 0.4 mm thickness, and fast speed show better elongation performance than other samples, according to Young’s modulus results. The SEM results for microscopic analysis show that samples S2 (loose infill, 45◦ orientation, 0.3 mm thickness, and normal speed), S5 (solid infill, 45◦ orientation, 0.3 mm thickness, and normal speed), and S8 (hollow infill, 45◦ orientation, 0.3 mm thickness, and normal speed) had a highly packed structure and robust. Discovering the parameter settings that could lead to greater mechanical and physical characteristics would undoubtedly assist designers and manufacturers worldwide as the FDM 3D printer becomes more and more crucial in manufacturing engineering parts.